Functional characterization of MEL-28/ELYS - Gómez-Saldivar, Georgina; Askjaer, Peter (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2013)
The nuclear envelope (NE) is a highly regulated membrane barrier that separates the nucleus from the cytoplasm in eukaryotic cells. Although the NE enables complex levels of gene expression, it also poses a challenge during cell division. To allow access of the mitotic spindle to chromatin, the NE of metazoans completely disassembles during mitosis, generating the need to re-establish the nuclear compartment at the end of each cell division. MEL-28/ELYS is essential for proper NE assembly in various organisms, such as Xenopus, C. briggsae and C. elegans. Previous studies have shown that MEL-28/ELYS is located at nuclear pore complexes during interphase, to kinetochores in early mitosis and subsequently during late mitosis it is widely distributed on chromatin. C. elegans mel-28 mutant embryos are affected in various cellular processes, such as segregation of chromatin, nuclear-cytoplasmic transport and reassembly of the NE (Galy et al., 2006), whereas mutant zebrafish show defects in intestinal, liver, pancreas, and eye development. However, the mechanism of action of MEL-28 is not known, nor is it clear where and how MEL-28 binds to DNA during mitosis and NE assembly. In order to identify and characterize the location of protein domains that interact with chromatin we have constructed mutants expressing different fragments of MEL-28 fused to GFP protein. Likewise, DamID (van Steensel & Henikoff, 2000) assay was performed for identifying regions of chromatin to which joins MEL-28 and determining whether binding sites follow a specific pattern. Vincent Galy, Peter Askjaer, Cerstin Franz, Carmen López-Iglesias and Iain W. Mattaj. 2006. MEL-28, a Novel Nuclear-Envelope and Kinetochore Protein Essential for Zygotic Nuclear-Envelope Assembly in C. elegans. Current Biology, Vo 16. Pp 1748–1756. Bas van Steensel and Steven Henikoff. 2000. Identification of in vivo DNA targets of chromatin proteins using tethered Dam methyltransferase. Nature Biotechnology, Vol 18. Pp 424-428.